The National Health Insurance Act 20 of 2023 : navigating constitutional obligations and the risk of regulatory overreach. - Grove, N.J. (University of Pretoria, 2025)
Mini-dissertation (LLM (Insurance Law and Governance))--University of Pretoria, 2025.